Interpretando "mundos": jogos digitais & aprendizagem histórica - Santos, Bergston Luan (2014)
A cursory look at video games and youth can often prove readings and simplistic conclusions. However, this research aimed to deepen that \"look\" and investigates the possibilities of historical learning mediated by digital games. We intend the possibilities that digital game play in the production of interpretation made by the players was cover, this interpretation is apprehended in this work by learning in history bias, interpretation as a cognitive exercise. To do so, we use a qualitative approach as a tool for data collection was used questionnaires, interviews and observation. Since these instruments were provided an opportunity us gather information on young people and their relationship with video games. In this work we seek to understand the youth beyond the socially hierarchical stereotypes, understanding it as a phase of life itself, not just intermediate moment between childhood and adulthood. Regarding learning, we address this concept by cultural-historical perspective which provided an opportunity to think of learning as a product of social relations thus suggest that learning is part of an integral dimension of social practice. The purpose of learning history as a thesis employ the idea that this is not something innate in the human being, on the contrary, we believe there is need for external stimuli to learn history. When discussing digital games and learning shared the idea that video games are not just objects of time passes, instead, are objects of culture and need to be investigated in order to better understand the relationships that mediate with the player. Finally, we also discussed in this paper on the interpretation in history, for this task, we use the work of Ricoeur (2007) and (2011) and de Certeau (1982), where we discuss the interpretation in history must be understood as part of the cognitive manifestations, and that are important in the work of thinking historically. Finally, the study revealed that digital games are objects of historical theme of culture capable of mediating situations that lead players to think and interpret situations and representations that suggest past. However, there is a need to deepen the debate about history in school and from the media in order to offer more critical about the relationship of history to the screen representations of the subjects mental operations.